Analysis of the Role of Packaging in Increasing Product Marketing for Family Berkah Micro, Small and Medium Enterprises (MSMEs) - Putri, Syahmalia; Mubarak, Husni (Program Pascasarjana STIE Amkop Makassar, 2024)
This research was conducted at the UMKM Family Berkah. The aim of this research is to determine the role of packaging in improving the marketing of Family Berkah micro, small and medium enterprises (MSMEs) products. This study used descriptive qualitative method. Qualitative is the process of systematically searching and compiling data obtained from interviews, field notes and other materials so that they can be easily understood and the findings can be informed to others. The data collection methods used in this research are observation and interviews. Data analysis in this research uses the Miles and Hubermen model method. During the data collection process, 3 important activities were carried out, namely data reduction, data presentation, verification. There are four stages in this research, namely the pre-field stage, field work stage, data analysis stage and report writing stage. Packaging that meets business criteria can increase marketing, sales and buying interest for consumers, then increase market power, increase consumer trust, and expand marketing reach. The results of this research are that packaging displays that are very attractive to consumers will increase sales of the company's products.